Windows netbooks the path to low-cost computing - Kelly, James Floyd (Apress, 2009)
Information on buying and using a Windows netbook
Description based on print version record. - Includes index
The netbook -- Netbook hardware options -- Netbook maintenance -- Netbook software options -- Netbook and Google Docs -- Netbook malware protection -- Netbook web browsers -- Netbook email -- Netbook calendar -- Netbooks and OpenOffice.org -- Windows 7 and netbooks -- Finding great netbook apps -- Netbook manufacturers -- Upgrading a netbook to Windows 7 -- Additional netbook apps to consider
Keywords: Netbook computers / Handbooks, manuals, etc; Laptop computers / Handbooks, manuals, etc; Netbook-Computer